RISK FACTORS AND PROGNOSIS IN CHILDREN WITH CARDIOMYOPATHY - Efimenko Oksana Vladimirovna; Khaidarova Lola Rustamovna (Scholar Express Journals, 2023)
Cardiomyopathies remain one of the least studied and most difficult problems in pediatric cardiology. The manifestation of cardiomyopathies can develop at any age and range from asymptomatic forms to pronounced clinical manifestations with a poor prognosis. One of the most common in children is dilated cardiomyopathy, and the most insidious is hypertrophic, which often ends in sudden cardiac arrest. Restrictive cardiomyopathy, which is detected during targeted examination, is quite difficult in terms of diagnosis. Noncompact cardiomyopathy is a frequent, but poorly understood, cardiomyopathy, in most cases complicated by arrhythmic syndrome
Keywords: dilated; hypertrophic; restrictive; heart failure